WHAT ARE THE BARRIERS TO THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS? A REVIEW OF RECENT STUDIES - Nurvita Wikansari; Dian Budi Santoso (Poltekkes Kemenkes Semarang, 2022)
Information technology utilization in the health sector is increasingly widespread. One aspect that cannot be separated from the intervention of information technology is medical records management through electronic medical records implementation. The number of healthcare facilities that implement electronic medical records is increasing. However, it is important to understand the various barriers that may be encountered in the electronic medical records implementation so that the success rate of implementation will be higher. This study aims to identify the current state of knowledge about electronic medical records implementation barriers. A literature review was conducted using three databases, PubMed, Science Direct, and Google Scholar using